Reframing E-Government Research in Qatar: A Systematic Review of Digital Governance and Institutional Transformation - Ashaari, Muhamad Faisal; Al-Sulaiti, Nouf Abdullah; Mokhtar, Ahmad Irdha (International Review of Management and Marketing, 2026)
This study examines the development of e-government research in Qatar within the broader context of digital transformation under the Qatar National Vision 2030. Despite significant progress driven by sustained investments in digital infrastructure, integrated information systems, and public service modernisation, the academic landscape remains fragmented, with limited synthesis on the role of data and information processes in shaping digital governance outcomes. To address this gap, this study adopts a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework, analysing 14 selected articles from Scopus and Web of Science published between 2016 and 2026. The findings reveal a strong dominance of technology adoption-oriented studies grounded in models such as the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), focusing on user intention, satisfaction, and system quality. However, limited attention has been given to data governance, information integration, and evidence-based decision-making. Governance-related perspectives, including inter-agency coordination, digital inclusivity, and bureaucratic fragmentation, are emerging but remain insufficiently operationalised. Overall, the study highlights gradual thematic expansion alongside continued theoretical and methodological concentration, underscoring the need for deeper empirical engagement with institutional and data-centric dimensions of digital transformation.